Divergence and species discrimination in freshwater bryozoans (Bryozoa: Phylactolaemata). (24th April 2013) - Hartikainen, Hanna; Waeschenbach, Andrea; Wöss, Emmy; Wood, Timothy; Okamura, Beth
<x xml:space="preserve">Abstract</x> We explored the suitability of nuclear and mitochondrial ribosomal markers [small subunit nuclear ribosomal RNA gene, large subunit nuclear ribosomal RNA gene, and a region spanning partial small mitochondrial ribosomal RNA subunit, four transfer RNA genes, and partial large mitochondrial ribosomal RNA subunit (referred to as rrnS‐rrnL)] for resolving patterns of diversification of 27 freshwater bryozoan species (class: Phylactolaemata) and evaluated the utility of statoblast ultrastructural features and molecular phylogenies for species discrimination in the Fredericellidae and Plumatellidae. Molecular data identified Plumatella fruticosa as distinct from the rest of the plumatellids, rendering the latter polyphyletic. rrnS‐rrnL was the most suitable marker for species discrimination and identified two undescribed species of Plumatella and at least two undescribed species of Fredericella. Lack of wide dispersal by fredericellid statoblasts may underlie the observed propensity for cryptic speciation and phylogeographical structure in Fredericella. Conversely, the strong dispersal potential of plumatellid statoblasts may mediate efficient gene flow between distant populations and explain the relatively low intraspecific divergence and lack of evidence for cryptic speciation. We show that species identification based on external features of statoblasts can be problematic in both genera, including for a putatively highly invasive, biofouling species, Plumatella vaihiriae, thereby highlighting the utility of rrnS‐rrnL sequences for species barcoding. © 2013 The Linnean Society of London